Digital transformation, for better or worse: a critical multi‐level research agenda. (17th March 2022) - Dąbrowska, Justyna; Almpanopoulou, Argyro; Brem, Alexander; Chesbrough, Henry; Cucino, Valentina; Di Minin, Alberto; Giones, Ferran; Hakala, Henri; Marullo, Cristina; Mention, Anne‐Laure; Mortara, Letizia; Nørskov, Sladjana; et al.
Abstract : For better or worse, digital technologies are reshaping everything, from customer behaviors and expectations to organizational and manufacturing systems, business models, markets, and ultimately society. To understand this overarching transformation, this paper extends the previous literature which has focused mostly on the organizational level by developing a multi‐level research agenda for digital transformation (DT). In this regard, we propose an extended definition of DT as "a socioeconomic change across individuals, organizations, ecosystems, and societies that are shaped by the adoption and utilization of digital technologies." We suggest four lenses to interpret the DT phenomenon: individuals (utilizing and adopting digital technologies), organizations (strategizing and coordinating both internal and external transformation), ecosystems (harnessing digital technologies in governance and co‐producing value propositions), and geopolitical frameworks (regulating the environments in which individuals and organizations are embedded). Based on these lenses, we build a multi‐level research agenda at the intersection between the bright and dark sides of DT and introduce the PIAI framework, which captures a process of perception, interpretation, and action that ultimately leads to possible impact . The PIAI framework identifies a critical research agenda consisting of a non‐exhaustive list of topics that can assist researchers to deepen their understanding of the DT phenomenon and provide guidance to managers and policymakers when making strategic decisions that seek to shape and guide the DT.